Administrative Services’ Effectiveness in Mokupa INPRES Primary School, Tombariri District, Minahasa Regency - Yudi Darsono; Nia Sumiati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to determine and analyze the effectiveness of administrative services at the Mokupa INPRES Elementary School, Tombariri District, Minahasa Regency. The aspects examined in this study consist of: 1) Administrative Service Process, namely: a) administrative service procedures, b) speed in performing administrative services (corresponding completion), c) accuracy in performing administrative services (accuracy in typing correspondence). ) d) service provider style. 2) The obstacles that arise in administrative services at the Mokupa INPRES Elementary School, Tombariri District, Minahasa Regency, namely: a) facilities and infrastructure, b) room temperature and maintenance c) administrative service room. The research method used in this research is descriptive qualitative method, while data collection techniques are carried out by means of observation, interviews, and documentation to the Principal, Administrative Staff, Teachers, Students and Parents of students. The results of this study indicate that Administrative Services in the Administrative Section at the Mokupa INPRES Elementary School, Tombariri District, Minahasa Regency are not yet fully effective. This is proven by not having competent administrative staff with civil servant status, and inadequate infrastructure so that administrative services often experience delays in the correspondence completion process and are less thorough in typing correspondence.